A comparison of conventional external radiotherapy technique and conformal radiotherapy technique in terms of acute toxicity with regard to hormonal treatment - (:unkn) unknown (My University, 2004)
Objective: Comparing the application of conventional external radiotherapy technique (EBRT) and conformal radiotherapy technique (CRT) in terms of acute side effects with respect to hormonotherapy (HT) in the primary treatment of prostate cancer. Materials and Methods: Seventy-five patients diagnosed with localized prostate cancer were treated with primary radiotherapy (RT) between March 1997 and July 2002, 47 with EBRT and 28 with CRT. 23 patients (31%) did not receive HT, 22 patients (29%) received concomitant HT (CHT) and 30 patients (40%) received neoadjuvant HT (NAHT). The patients were observed for at least 3 months and the acute toxicity was evaluated by EORTC/RTOG (European Organization for Research and Treatment of Cancer / Radiation Therapy Oncology Group) scale 1. Results: There was no grade III-IV acute urinary and rectal toxicity. The percentage of grade I and II acute urinary toxicity was determined as 30% and 23%, respectively in the EBRT group. The ratios were 61% and 18%, respectively in the CRT group (p=0.025). Grade II urinary toxicities were 13% in patients who did not receive HT and who received NAHT, 41% in patients who received CHT (p=0.02). Grade II rectal toxicities were 30% for EBRT and 7% for CRT group (p=0.022). Conclusion: CRT caused a decrease in grade II rectal and urinary toxicity. Grade II acute urinary toxicities were observed more frequently in the treatment of CHT than the NAHT.
Keywords: Acute toxicity; Cconventional-conformal radiotherapy; Prostate cancer